Implementing ISO 9001:2015 : thrill your customers and transform your cost base with the new gold standard for business improvement /: thrill your customers and transform your cost base with the new gold standard for business improvement. (2015) - Gillett, Jan; Simpson, Paul (John Paul), 1961-; (Executive coach), Clarke, Susannah
No abstract available